(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research proposes the construction of a model of technological surveillance for the strategic management of scientific research in higher education institutions in Colombia. This model is composed by an information system that includes scientific articles, intervention plans for the regions and the nation, and information from public policies related to Science, technology, and information (STI). From this data set, the construction of algorithms for information processing was carried out, using techniques of automatic text analysis and natural language processing with complex networks to detect patterns and the configuration of trends related to science, technology, research, and innovation, which are the guiding topics of the national science and technology system. The main results obtained in this research are that the construction of a complex system revealed the topics on which scientific production is focused in the country. In addition, the analysis of the documents related to STI referenced in in public policies analyzed for this research revealed the pressing needs of different sectors and regions in the country. Finally, the research showed that the topics on which scientific research in Colombia is conducted by the educational institutions of the country does not correspond to the needs found.